Simultaneous non-Hodgkin lymphoma of the external auditory canal and thyroid gland: A case report - Khaw, B.L.; Sivalingam, S.; Pathamanathan, S.S.; Tan, T.S.; Naicker, M. (Vendome Group, LLC, 2014)
Approximately 25% of all cases of extranodal non-Hodgkin lymphoma (NHL) occur in the head and neck region; NHL of the external auditory canal (EAC) and thyroid gland are rare. Specific immunohistochemical staining of the excised tissue is required to confirm the final pathologic diagnosis. We report the case of a 53-year-old woman with underlying systemic lupus erythematosus and autoimmune hemolytic anemia that were in remission. She presented with chronic left ear pain, a mass in the left EAC, and rapid growth of an anterior neck swelling that had led to left vocal fold palsy. High-resolution computed tomography (CT) of the temporal bone and CT of the neck detected a mass lateral to the left tympanic membrane and another mass in the anterior neck that had infiltrated the thyroid gland. The patient was diagnosed with simultaneous B-cell lymphoma of the left EAC and thyroid gland. She was treated with chemotherapy. She responded well to treatment and was lost to follow-up after I year. To the best of our knowledge, the simultaneous occurrence of a lymphoma in the EAC and the thyroid has not been previously described in the literature.